Technical evaluation of the polyculture of shrimp (Litopaneaus vannamei) and red tilapia (Oreochromis spp.) in saline water using substrate in Zamorano, Honduras - Salas G., Roberto P. (Escuela Agrícola Panamericana,Zamorano, 2014)
Marine shrimp and tilapia are the most important species for aquaculture in Latin America. The objective was to evaluate the production parameters in the monoculture of shrimp and the shrimp-tilapia polyculture. This experiment was carried out using 12 concrete tanks (3 × 2.5 × 0.8 m), a layer of sand (5 cm) and 17 softdrink crates. The tanks were filled with saline water (10,000 and 50 ppm with crude salt and KCl, respectively). Each tank had artificial aeration and was covered with transparent plastic. The treatments were a shrimp monoculture and two shrimp-tilapia polycultures 2 and 4 fish/m3. The shrimp stocking density in all treatments was 60/m3 and the tilapias were stocked 23 days after the shrimp. The shrimp and tilapia were fed with pelleted feed with 32 and 28% of crude protein, respectively; the amount offered was calculated according the biomass in each tank. The experiment lasted 92 days; every 23 days, 10% of each population was sampled. The experiment was a Completely Random Design with four replicates per treatment. The data on production parameters were analysed by an ANOVA and a separation of means (SNK). A production budget for the treatments was done to calculate the utility of each. Concerning water quality, only dissolved oxygen and ammonia did not fall within acceptable ranges. The average shrimp weight gain, length growth and survival were 1 g/week, 8 mm/week and 10%, respectively; there was no significant difference between treatments (P<0.05). The average tilapia weight gain, length growth and survival were 10 g/week, 14 mm/week and 84%, respectively. Significant differences (P<0.05) were observed in tilapia average weight and biomass between the polycultures, but none in the average length and survival. The tilapias competed with shrimp for the feed. All treatments generated economic losses. Tilapia does not affect production parameters of shrimp.